An HDAC8-selective fluorescent probe for imaging in living tumor cell lines and tissue slices. Issue 38 (16th September 2021) - Yan, Yinyu; Huang, Chaoqun; Shu, Yi; Wen, Hongmei; Shan, Chenxiao; Wang, Xinzhi; Liu, Jian; Li, Wei
Abstract : The fluorescence intensity of the HDAC8-selective fluorescence probe correlated well with the level of HDAC8 expression in living tumor cells and tissue slices. Abstract : Histone deacetylase 8 (HDAC8) has been used as a therapeutic target for many cancers as it is highly expressed in neuroblastoma cells and breast cancer cells. HDAC8-selective fluorescent probes need to be urgently developed. Herein, two novel fluorescent probes, namely NP-C6-PCI and AM-C6-PCI, based on the conjugation of 1, 8-naphthalimide with a highly selective inhibitor of HDAC8 (PCI-34051 ) were reported. Compared with PCI-34051 ( K D = 6.25 × 10 −5 M), NP-C6-PCI ( K D = 8.05 × 10 −6 M) and AM-C6-PCI ( K D = 7.42 × 10 −6 M) showed great selectivity toward HDAC8. Two fluorescent probes exhibited high fluorescence intensity under λ ex = 450 nm and a large Stokes shift (100 nm). NP-C6-PCI was selected for cell and tissue imaging due to the similarity in the bioactivity of NP-C6-PCI with PCI-34051 . The ability of NP-C6-PCI to target imaging HDAC8 in SH-SY5Y and MDA-MB-231 tumor cells was demonstrated. Furthermore, NP-C6-PCI was applied to imaging SH-SY5Y tumor tissue slices to indicate the relative expression level of HDAC8. Therefore, this HDAC8-selective fluorescent probe can be expected for applications in HDAC8-targeted drug screening as well as in pathologic diagnoses.